The complete mitochondrial DNA analyses of Inner Mongolia Cashmere goat type of Erlangshan species. Issue 1 (2nd January 2018) - Ma, Yuhao; Su, Rui; Fan, Yixing; Qiao, Xian; Li, Xiaokai; Zhang, Lei; Li, Jinquan
Abstract: Inner Mongolia Cashmere goat is evolved from Mongolia goat in long-term breeding, as a source of high-quality cashmere, Inner Mongolia Cashmere goat type of Erlangshan is famous in the world. By using molecular biology techniques, we sequenced the complete mitochondrial DNA of Erlangshan Cashmere goat. The complete length of sequence is 16, 640 bp, containing 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and a control region (D-loop region). Our mitogenome will enlarge genomic information for further studies on evolution and domestication of Inner Mongolia Cashmere goat, enhance germplasm conservation and breeding programs of domestic goat.